Enhancing disaster response of emergency medical teams through "TEAMS 3.0" training package-Does the multidisciplinary intervention make a difference? - Arielle Kaim; Arielle Kaim; Moran Bodas; Moran Bodas; Nieves Amat Camacho; Nieves Amat Camacho; Kobi Peleg; Luca Ragazzoni (Frontiers Media S.A., 2023)
BackgroundIn the aftermath of disasters, Emergency Medical Teams (EMTs) are dispatched to help local rescue efforts. Although EMTs are recognized to be a critical component of the global health workforce, concerns have emerged over their functioning and effectiveness. For example, lack of cooperation and coordination between different EMTs has been a longstanding issue, resulting in fragmented disaster management.MethodsTo enhance the provision of EMT's field teamwork, the Training for Emergency Medical Teams and European Medical Corps (TEAMS) project was established, and later further updated with novel scenarios and exercises (i.e., adapting EMT operations to a sudden disaster; becoming a modular team; reflecting on ethical dilemmas) in the complementary "TEAMS 3.0" project where a more comprehensive training package was developed. The aim of this study was to assess the effectiveness and quality of the TEAMS 3.0 training package in four training programs in Portugal, Germany, Norway, and Turkey. Participants completed a set of questionnaires designed to assess self-efficacy, teamwork, and quality of training.ResultsThe results from all the trainings suggest an improvement for both teams' self-efficacy and teamwork. The mean score among all the participants (N = 100) for both the self-efficacy scale and teamwork scale was 3.217 (±0.223) prior to training and 3.484 (±0.217) following the training, and 2.512 (±1.313) prior to training and 3.281 (±0.864), respectfully, with statistically significant differences according to Wilcoxon paired samples test (p < 0.05). The quality of training is regarded as high and deemed as an appropriate tool package for addressing the objectives of the project and the perceived needs of EMT disaster deployment.ConclusionThus far, the TEAMS 3.0 project has demonstrated to be effective in promoting EMT teamwork capacities.